A NOTE ON THE OCCURRENCE OF PARAFILARIOSIS IN A NON-DESCRIPT BULLOCK - C. Balachandran; N. Pazhanivel; A. Raman (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Parafilariosis, a parasitic infection in cattle caused by Parafilaria bovicola, is characterized by nodules and bleeding points. It causes cutaneous bleeding of live cattle and bruise-like lesions in the subcutaneous and intramuscular surface of the affected carcasses (Bech-Nielsen et al., 1982). This condition is sporadically reported in India. Occurrence of parafilariosis in a non-descript bullock and its successful treatment are reported.